AB0700 Is it feasible to withdraw immunosuppressive treatment in real-life patients with anca-associated vasculitis?. (12th June 2018) - Monti, S.; Vitolo, B.; Balduzzi, S.; Felicetti, M.; Padoan, R.; Berti, A.; Bond, M.; Quartuccio, L.; Paolazzi, G.; Schiavon, F.; Montecucco, C.; Caporali, R.
Abstract : Background: The optimal duration of remission-maintenance treatment in ANCA-associated vasculitis (AAV) is still unknown, 1 with International recommendations suggesting to maintain it for at least 24 months. Data supporting the correct balance between relapse risk, treatment-related adverse events and damage are highly needed. Objectives: To analyse the frequency and predictors of withdrawal of remission-maintenance immunosuppressive drugs (IS) in a large real-life cohort of AAV patients. Methods: Clinical records of patients with granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA) were retrospectively analysed from a multicentric cohort. We divided the cohort into group A (withdrawal) and group B (ongoing). Results: We included 185 patients. Forty-one patients (22%) had withdrawn IS at the end of follow-up (median 73.5 months, IQR 54–115). Concomitant glucocorticoids were stopped in 33%. There were no significant differences in AAV subtype, ANCA pattern, age at diagnosis, diagnostic delay or comorbidities rates between group A and group B (table 1). Disease onset with pulmonary involvement was significantly more frequent in patients in whom IS was maintained (69.7% vs 45%; p=0.004). Figure 1. Disease activity at onset, but not during follow-up, was significantly higher in patients from group B (ongoing): median BVAS 18 (12–24) vs 15; (8–20) p=0.02. The type of IS used for remission induction did not differ between the two groups. Maintenance treatment with Rituximab (RTX) was associated with higher probability of discontinuing IS by the end of follow-up (21% vs 7.6%; p=0.02). There was no difference in the number of major relapses between the two groups. Safety profile was equally good in both groups, except for a higher number of infections over the course of disease in patients who withdrew IS (5% vs 0). Vasculitis damage index (VDI) was comparable between the two groups. Conclusions: IS withdrawal was observed in a minority of real-life patients with AAV. Drug-free remission was negatively associated with pulmonary involvement and higher BVAS at disease onset. Remission maintenance with RTX was associated with a higher frequency of drug withdrawal at the end of follow-up. Reference: [1] Karras, et al. Randomised controlled trial of prolonged treatment in the remission phase of ANCA-associated vasculitis. Ann Rheum Dis2017;76:1662–68 Disclosure of Interest: None declared